Kesadaran Hukum Dalam Pemenuhan Hak Disabilitas Perspektif Hukum Keluarga - Nuraini, Diah; Solichin, Nur Mifchan; Umam, Khotibul (Jurnal EL-QANUNIY: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2024)
Legal awareness in disabled families shows a fifty-fifty point, where someone with a disability has the courage to try to get married and fulfill their rights and obligations as a husband, especially the right to support their family. Although not all blind families know and understand the details of marriage law such as marriage conditions, rights and obligations of husband and wife, child gifts, as contained in applicable family law principles. Efforts to work coupled with skills and job opportunities have grown significantly, in Indonesia in 2022, there will be 720,748 disabled workers, an increase from 277,018 people in 2021. On the other hand, awareness of disability law in the public sphere is still lacking, where it is still limited. access to facilities and infrastructure at Special Schools and Community Learning Activity Centers at the village level which motivates increasing insight and skills with disabilities as an improvement in living standards, whereas in the realm of legal apparatus, judiciary and correctional institutions, there is minimal implementation of the fulfillment of disability rights, such as supporting facilities for sign language interpreters and the use of Braille, disabled-friendly building facilities and legal information outreach to people with disabilities.